Teaching Aids in Mathematics and Manual for their Construction - MAURYA, R.P. (SCHOOL SCIENCE, 2006)
The world of mathematics provides an unlimited scope to mathematicians to percive problems pertaining to three situations visualised in the forms of concrete, abstraction and intuition. However due to abstraction and intuition some of the mathematical concepts become more complicated sometimes even for teachers also who are actively engaged in mathematics teaching at different stages. This needs the exhaustive training in methods as well as in contents. This also needs the clarifications of mathematical concepts using teaching aids, eperimentation, observation and practicals etc. in mathematics to avoid the abstraction at different stages of schooling.